Restoring forests and trees for sustainable development policies, practices, impacts, and ways forward - Katila, Pia ca. 20./21. Jh; Colfer, Carol J. Pierce 1945-; Jong, Wil de 1956-; Galloway, Glenn ca. 20./21. Jh; Pacheco, Pablo (Oxford University Press, 2024)
This book takes a multidisciplinary perspective to analyze and discuss the various opportunities and challenges of restoring tree and forest cover to address regional and global environmental challenges that threaten human well-being and compromise sustainable development. It examines forest restoration commitments, policies and programs, and their planning and implementation at different scales and contexts, and how forest restoration helps to mitigate environmental, societal, and cultural challenges. The chapters explore the concept of forest restoration, how it can restitute forest ecosystem services, contribute to biodiversity conservation, and generate benefits and synergies, while recognizing the considerable costs, trade-offs, and variable feasibility of its implementation. The chapters review historic and contemporary forest restoration practice and governance, variations in approaches and implementation across the globe, and relevant technological advances. Using the insights from the ten topic-focused chapters, the book reflects on the possibility of sustainable and just approaches to meet the challenges that lie ahead to achieve ambitious international forest restoration targets and commitments.